The geodynamic setting in the northwest circumference of the Pacific Ocean: Effects on the dynamics of subsurface radon and on the gas composition of the heat carrier at the Mutnovskii geoelectric power station - Firstov P.P.; Makarov E O.; Maksimov A.P.; Chernev I.I. (My University, 2015)
This paper provides information on the behavior of the radon activity time series for the period from 2000 through 2015 in the water-saturated zone of the Paratunka Geothermal Field and that of the time series that recorded the volumetric fraction of molecular hydrogen in the gaseous heat carrier at well 016 in the Mutnovskii Field, as well as their relationships with the seismicity in the northwestern circumference of the Pacific Ocean. It was concluded that long-term trends in radon activity and the high volumetric fraction of molecular hydrogen in 2014 are caused by a change in the stress field that acts in the subduction zone of the northwest flank of the Pacific Ocean. It is hypothesized that an M > 7.5 earthquake is likely to occur during the next 1.5 years. In the opinion of Academician S.A. Fedotov, the most likely location for such an event is between the Shipunskii Peninsula and Shiashkotan Island, Middle Kuril islands.
Keywords: Mutnovskii Geoelectric Power Station; Subsurface Radon